2014
DOI: 10.1103/physreve.89.043306
|View full text |Cite
|
Sign up to set email alerts
|

Numerical calculation of interaction forces between paramagnetic colloids in two-dimensional systems

Abstract: Typically the force between paramagnetic particles in a uniform magnetic field is described using the dipolar model, which is inaccurate when particles are in close proximity to each other. Instead, the exact force between paramagnetic particles can be determined by solving a three-dimensional Laplace's equation for magnetostatics under specified boundary conditions and calculating the Maxwell stress tensor. The analytical solution to this multi-boundary-condition Laplace's equation can be obtained by using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…However, it has also been shown that the many-body effect becomes negligible once you are sufficiently far away from the edge of a cluster or chain. 42 Thus, we analyze only chains of greater than 30 beads.…”
Section: Image Processing and Fourier Mode Analysismentioning
confidence: 99%
“…However, it has also been shown that the many-body effect becomes negligible once you are sufficiently far away from the edge of a cluster or chain. 42 Thus, we analyze only chains of greater than 30 beads.…”
Section: Image Processing and Fourier Mode Analysismentioning
confidence: 99%
“…. ,N. Nevertheless the MDM's neglect of multipolar effects leads to a significant deviation in the calculated force in the near field [17]. The multipolar effects are caused by the asymmetric magnetization inside the spheres when they are placed close 1539-3755/2014/90(3)/033310 (5) 033310-1…”
mentioning
confidence: 99%
“…The solution to the Laplace equation can be analytically approximated by a solid harmonics expansion with the Hobson formula applied to unify the coordinate system [14,16]. This coordinate unification is very computationally expensive and suffers from singularity-related issues [17,18]. A numerical solution to Laplace's equation can be obtained by using a smoothed representation of susceptibility to replace the boundary conditions [17]; this method is referred to as the Laplace equation solver (LES) method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to such a complex dipolar magnetism involving all existing particles in a ferrofluid, the corresponding numerical analysis is often simplified into a two-particle system. [27][28][29] Therefore, we present an alternative experimental method of indirectly identifying the change in potential energy [ÁUð" rÞ] by characterizing relaxation responses of suspended particles. Numerical analysis of this parameter enables the estimation of (b) hydrodynamic size distributions indicating the secondary particle clustering at 30 wt % ferrofluid sample.…”
Section: Ion Concentration-dependent Electrostatic Interparticle Intementioning
confidence: 99%